Las funciones y las relaciones sociales, económicas y políticas de los miembros del Cabildo Catedralicio de la Diócesis de Nicaragua y Costa Rica (1531-1859) - Velázquez Bonilla, Carmela (2008)
The article analyzes the functions of the cathedral chapter of the Diocese of Nicaragua and Costa Rica with the purpose of explaining the social, political and economic relations of its members and determining the importance of the chapter in the operation of the diocese between the years 1531 and 1859. Colonial primary sources, including testaments and tithe registers, among others, reveal that the members of the cathedral chapter of Leon had specific functions within the diocese, both when the see was vacant and when there was a Bishop in office. The members of the cathedral chapter did not constitute a capitular body isolated from the rest of society. Rather, they maintained economic and social relations of trust among themselves and with the society that surrounded them. Therefore, they were a capitular body crucial to the operation of the diocese, both when they served as the bishops advisory committee and when they governed the diocese in the absence of a Bishop.